FAKTOR PENGHAMBAT PENGELOLAAN RUANG TERBUKA HIJAU (RTH) DI KOTA JAMBI - Ananda Putri Rohima (Gapenas Publisher, 2022)
This research discusses the management of Green Open Space (RTH) in Jambi City, especially what are the inhibiting factors in the management of the RTH so that the amount of RTH area in Jambi City is still far from the targeted standards and the quality of RTH is still not good. This type of research is qualitative descriptive research. The type of data used in this study is primary data obtained from interviews with research informants and secondary data in the form of reports and official documents. Data collection techniques used in the form of interviews, observations and documentation. The data analysis technique used is descriptive analysis that uses interpretation of the data, facts and information obtained. The results of this study show that the management of the green open space of Jambi City has not been done to the maximum. This is because there are inhibitory factors that in this study are seen from institutional aspects, financing and participation. In the institutional aspect seen from the component of rules / policies where in managing RTH refers to RPJMD and RTRW Kota Jambi which then each SKPD makes a Strategic Plan (Renstra-SKPD). But there is still a lack of regulations that protect RTH so that there are risks such as diversion of functions, unlicensed felling of trees and so on. Furthermore, in the financing aspect, funds sourced from APBD have met the standards, but the use of funds carried out is not appropriate such as focusing more on improving supporting facilities and not on improving and managing RTH. Participation that has not been done optimally by both the private sector and the public is also an inhibitory factor in the process of managing Green Open Space (RTH) in Jambi City.